Combination of lenalidomide with vitamin D3 induces apoptosis in mantle cell lymphoma via demethylation of BIK - Brosseau, C (Cell Death Dis, 2014)
Mantle cell lymphoma (MCL) is a currently incurable B-cell malignancy. Lenalidomide (Len) has been demonstrated to be one of the most efficient new treatment options. Because Len and 1α,25-dihydroxyvitamin (VD3) synergize to kill breast cancer cells, we investigated whether VD3 could increase the ability of Len to induce MCL cell death. While MCL cells were weakly sensitive to Len (1 μM), the addition of VD3 at physiological dose (100 nM) strongly increased cell death, accompanied by slowdown in cell cycle progression in MCL cell lines (n=4 out of 6) and primary samples (n=5 out of 7). The Len/VD3 treatment markedly increased the expression of the BH3-only BCL2-interacting killer (Bik) without affecting the expression of other Bcl-2 molecules. Immunoprecipitation assays demonstrated that Bik was free from anti-apoptotic partners, Bcl-2 and Bcl-x(L), in treated cells. Moreover, silencing of BIK prevented apoptosis induced by Len/VD3, confirming the direct involvement of Bik in cell death. Bik accumulation induced by Len/VD3 was related to an increase in BIK mRNA levels, which resulted from a demethylation of BIK CpG islands. The sensitivity of MCL cells to Len/VD3 was similar to the response to 5-azacytidine, which also induced demethylation of BIK CpG islands. These preclinical data provide the rationale to investigate the role of VD3 in vivo in the response to Len.